Neutral Effects of Combined Treatment With GLP-1R Agonist Exenatide and MR Antagonist Potassium Canrenoate on Cardiac Function in Porcine and Murine Chronic Heart Failure Models - Demkes, Evelyne J.; Wenker, Steven; Silvis, Max J. M.; van Nieuwburg, Martijn M. J.; Visser, M. Joyce; Jansen, Marlijn S.; Brans, Maike A. D.; Velema, Evelyn; Sluijter, Joost P. G.; Hoefer, Imo E.; de Kleijn, Dominique P. V.; Timmers, Leo; et al. (Frontiers in Pharmacology, 2021)
Background: Ischemia reperfusion and cardiac remodeling is associated with cardiomyocyte death, excessive fibrosis formation and functional decline, eventually resulting in heart failure (HF). Glucagon-like peptide (GLP)-1 agonists are reported to reduce apoptosis and myocardial infarct size after ischemia reperfusion. Moreover, mineralocorticoid receptor antagonists (MRAs) have been described to reduce reactive fibrosis and improve cardiac function. Here, we investigated whether combined treatment with GLP-1R agonist exenatide and MRA potassium canrenoate could minimize cardiac injury and limit HF progression in animal models of chronic HF. Methods and Results: Forty female Topigs Norsvin pigs were subjected to 150 minutes balloon occlusion of the left anterior descending artery (LAD). Prior to reperfusion, pigs were randomly assigned to placebo or combination therapy (either low dose or high dose). Treatment was applied for two consecutive days or for 8 weeks with a continued high dose via a tunneled intravenous catheter, for the follow-up duration of 8 weeks. Using 2,3,5-Triphenyltetrazolium chloride (TTC) staining we observed that combination therapy did not affect the scar size after 8 weeks. In line, left ventricular volume and function assessed by three-dimensional (3D) echocardiography (baseline, 7 days and 8 weeks), and cardiac magnetic resonance imaging (CMR, 8 weeks) did not differ between experimental groups. In addition, 36 C57Bl/6JRJ mice underwent permanent LAD-occlusion and were treated with either placebo or combination therapy prior to reperfusion, for two consecutive days via intravenous injection, followed by continued treatment via placement of osmotic mini-pumps for 28 days. Global cardiac function assessed by 3D echocardiography performed at baseline, 7, 14, and 28 days did not differ between treatment groups. Also, no differences were observed in cardiac hypertrophy assessment by heart weight/bodyweight and heart weight/tibia length ratio. Conclusion: In the current study, combined treatment with GLP-1R agonist exenatide and MR antagonist potassium canrenoate did not show beneficial effects on cardiac remodeling nor resulted in functional improvement in a small and large animal chronic HF model.